The end-joining factor Ku acts in the end-resection of double strand break-free arrested replication forks - Ana Teixeira-Silva (Nature Portfolio, 2017)
Terminally arrested replication forks are restarted through homologous recombination after processing single-stranded DNA gaps. Here the authors show that resection is regulated by the NHEJ factor Ku, helping to fine-tune recombination at forks.